2014
DOI: 10.1111/resp.12384
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of airway smooth muscle remodelling in asthma: Relation to airway inflammation

Abstract: Background and objective: Pathological phenotypes of asthma have been based predominantly on inflammation, rather than airway wall remodelling. Differences in the distribution of airway smooth muscle (ASM) remodelling between large and small airways may affect clinical outcomes in asthma. The aim of this study was to examine the distribution of ASM remodelling and its relation to airway inflammation. Methods: Post-mortem cases of asthma (n = 68) were categorized by the distribution of increased thickness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 33 publications
(64 reference statements)
2
73
0
Order By: Relevance
“…Another study in smokers with severe asthma has shown a relationship between low sputum MMP-9/TIMP (tissue inhibitors of metalloproteinase) ratio, persistent airflow obstruction and reduced airway lumen on CT [57]. However, a post mortem study of fatal asthma patients showed increased smooth muscle was only associated with airway eosinophilia, but not neutrophilia [58]. It is therefore apparent that more assessments of airway structure and mechanistic studies are needed to better understand the relationship between neutrophils, MMP-9, lung function and remodelling, especially if MMP-9 might be a potential therapeutic target for neutrophil predominant disease.…”
Section: The Role Of Neutrophils In Asthma and Relationships With Remmentioning
confidence: 99%
“…Another study in smokers with severe asthma has shown a relationship between low sputum MMP-9/TIMP (tissue inhibitors of metalloproteinase) ratio, persistent airflow obstruction and reduced airway lumen on CT [57]. However, a post mortem study of fatal asthma patients showed increased smooth muscle was only associated with airway eosinophilia, but not neutrophilia [58]. It is therefore apparent that more assessments of airway structure and mechanistic studies are needed to better understand the relationship between neutrophils, MMP-9, lung function and remodelling, especially if MMP-9 might be a potential therapeutic target for neutrophil predominant disease.…”
Section: The Role Of Neutrophils In Asthma and Relationships With Remmentioning
confidence: 99%
“…6 This creates a paradox with the findings of the present study of post-mortem lung, which indicated that there were no differences in neutrophil density in the large airways between asthma and controls. 3 The current study also points out that airway smooth muscle remodelling, a central tenet of the modern asthma paradigm, was not present in 37% of cases, commonly but not exclusively, in the mild to moderate asthmatics.…”
mentioning
confidence: 48%
“…3 Airway smooth muscle thickening was associated with eosinophilia but not neutrophilia, and there were no significant differences in neutrophil density in the large airways of the 68 asthmatics compared with 37 controls studied, a considerable body of work. 3 This observation underscores the concept that neutrophilic inflammation in asthma may be very hard to determine. It is also likely that in vivo both cell counts and cellular activity will be important in pathophysiology.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…However, to date there has been no consensus on whether phenotypic differences in the ASM of asthmatics contributes to AHR (Gunst et al 2012;Paré and Mitzner 2012). While there is general agreement that there is a greater amount of ASM in mild/moderate, and especially in severe, asthma (Dunnill et al 1969;Ebina et al 1993;Woodruff et al 2004;Chin et al 2012;James et al 2012;Elliot et al 2014), it is unclear whether the hyperplastic/hypertrophied ASM behaves differently due to altered expression of genes for contractile, cytoskeletal, or inflammatory function.…”
Section: Introductionmentioning
confidence: 95%